Navigating the Mind of Young Investors: Behavioral Drivers of Investment Choices in Nepal - Sharma, Dilli Raj; Mahato, Bijay (KIC International Journal of Social Science and Management, 2024)
This thesis explores how psychological traits influence investment decisions among Generation Z and millennials in Nepal’s commercial banking sector. Focusing on trait anger, trait anxiety, overconfidence, herding, and self-monitoring, the study surveyed 388 respondents using a quantitative approach. Findings reveal that overconfidence, trait anger, and anxiety significantly shape young investors’ risk perception and financial choices, while herding and self-monitoring had minimal impact. The research underscores the need for financial education tailored to address behavioral biases, helping young investors make informed decisions. Despite its contributions, the study is limited by its cross-sectional design and narrow focus on bank employees. In the future, more research is needed on diverse populations using ongoing research to uncover changing investment habits. In general, the study shows important information about the psychology related to financial decision-making in Nepal.